Mitral valvotomy in childhood. Issue 4 (July 1973) - Gotsman, M. S.; Van Der Horst, R. L.; le Roux, B. T.; Williams, M. A.
Abstract : Gotsman, M. S., van der Horst, R. L., le Roux, B. T., and Williams, M. A. (1973) . Thorax, 453-457. Mitral valvotomy in childhood . During the seven-year period 1965 to 1972 mitral valvotomy for mitral stenosis was undertaken in 72 children aged 15 years or less. Excellent results were achieved from closed transventricular instrumental valvotomy unless the valve was calcified, there was a jet of mitral incompetence or a second valvotomy was being undertaken. Severe pulmonary arterial hypertension was present before operation and regressed after a successful valvotomy. There was a low incidence of overt antecedent rheumatic fever.